2012
DOI: 10.1111/j.1600-6143.2011.03915.x
|View full text |Cite
|
Sign up to set email alerts
|

Graft Vasculopathy in Clinical Hand Transplantation

Abstract: Allogeneic hand transplantation is now a clinical reality. While results have been encouraging, acute rejection rates are higher than in their solid-organ counterparts. In contrast, chronic rejections, as defined by vasculopathy and/or fibrosis and atrophy of skin and other tissues, as well as antibody mediated rejection, have not been reported in a compliant hand transplant recipient. Monitoring vascularized composite allograft (VCA) hand recipients for rejection has routinely involved punch skin biopsies, va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
149
1
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(157 citation statements)
references
References 35 publications
4
149
1
3
Order By: Relevance
“…One patient had to be switched from mycophenolate mofetil to sirolimus (in addition to tacrolimus and steroids) for nonresolving grade 2-3 rejection. 12 Chronic rejection or chronic allograft vasculopathy have not been reported; these disorders were previously considered possible and have become evident in human hand transplantation 44 and preclinical studies. 45 Hyperacute rejection from pre-formed antibodies has also not been reported.…”
Section: Immunological Outcomesmentioning
confidence: 99%
“…One patient had to be switched from mycophenolate mofetil to sirolimus (in addition to tacrolimus and steroids) for nonresolving grade 2-3 rejection. 12 Chronic rejection or chronic allograft vasculopathy have not been reported; these disorders were previously considered possible and have become evident in human hand transplantation 44 and preclinical studies. 45 Hyperacute rejection from pre-formed antibodies has also not been reported.…”
Section: Immunological Outcomesmentioning
confidence: 99%
“…In particular, the intracellular signaling pathways leading to endomune factors also contribute to TV, the majority of renal allograft loss due to chronic rejection was associated with HLA DSAs (24, 164). Chronic rejection is also an important cause of late failure of vascularized CTA (165,166). Similarly, chronic damage and TV in heart (25), lung (95,167,168), pancreas (169), and liver (11, 28, 170) allografts are more common among patients with a history of biopsy-proven AMR and HLA DSAs.…”
Section: Discussionmentioning
confidence: 99%
“…Aggressive and severe intima hyperproliferation was observed early post-transplant in two out of six of the recipients in their patient series. Of concern, standard monitoring techniques were inadequate to detect early potentially reversible stages of allograft vasculopathy in four out of the six recipients [94]. These data show that chronic rejection will be a topic in the next 5 years that requires due diligence and intense further investigation as we are expanding the number of transplants performed and about to develop novel treatment protocols for hand transplantation.…”
Section: Five-year Viewmentioning
confidence: 93%
“…However, in experimental rat hindlimb transplantation models, changes such as intimal hyperproliferation and luminal narrowing/occlusion consistent with chronic rejection or allograft vasculopathy have been shown after repeated episodes of acute skin rejection and frequent lapses in maintenance immunosuppression [93]. Most recently, Kaufman et al reported some level of vasculopathy in all six of their hand transplant recipients with aggressive and severe intimal hyperplasia observed early post-transplant in two patients [94]. Of concern, in four of their patients standard techniques used for surveillance of rejection (protocol skin biopsies, DSA and conventional vascular imaging modalities) were obviously inadequate for detecting early, potentially reversible, stages of allograft vasculopathy.…”
Section: Future Researchmentioning
confidence: 99%